2012
DOI: 10.1136/gutjnl-2011-300821
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent PEDF deficiency and Kras mutation induce invasive pancreatic cancer and adipose-rich stroma in mice

Abstract: These data highlight the importance of lipid metabolism in the tumour microenvironment and identify PEDF as a critical negative regulator of both adiposity and tumour invasion in the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 47 publications
6
71
0
Order By: Relevance
“…Pancreatic tumors from older, obese patients are marked by the presence of adipocytes and these patients have worse outcomes [6466]. Based on the observation that pancreatic cancers depend on glutamine metabolism for survival [67, 68], conditioned media from preadipocytes were also found to contain glutamine, which supported pancreatic cancer cell proliferation in glutamine-free growth media [69] (Fig.…”
Section: Intra-tumoral Metabolic Crosstalkmentioning
confidence: 99%
“…Pancreatic tumors from older, obese patients are marked by the presence of adipocytes and these patients have worse outcomes [6466]. Based on the observation that pancreatic cancers depend on glutamine metabolism for survival [67, 68], conditioned media from preadipocytes were also found to contain glutamine, which supported pancreatic cancer cell proliferation in glutamine-free growth media [69] (Fig.…”
Section: Intra-tumoral Metabolic Crosstalkmentioning
confidence: 99%
“…The expression levels of lipid droplet-associated proteins, tail-interacting protein 47 (TIP47), and adipose differentiation-related protein (ADRP) were increased, while the expression of adipose triglyceride lipase, a key enzyme in lipolysis, was decreased in the pancreatic stroma of EL-Kras G12D /PEDF-deficient mice. Compared with the EL-Kras G12D /PEDF wild-type mice, ELKras G12D /PEDF-null mice had higher frequencies of cystic papillary neoplasms and invasive pancreatic ductal adenocarcinoma (11). Their study shed the light on the mechanism of intrapancreatic fatty infiltration.…”
mentioning
confidence: 99%
“…However, the mechanism of intrapancreatic fatty infiltration in obese patients remains to be determined. A recent study by Grippo and colleagues (11) showed that knockout of pigment epithelium-derived factor (PEDF) in ELKras G12D mice resulted in increased intrapancreatic fatty infiltration and peripancreatic fat with adipocyte hypertrophy. The expression levels of lipid droplet-associated proteins, tail-interacting protein 47 (TIP47), and adipose differentiation-related protein (ADRP) were increased, while the expression of adipose triglyceride lipase, a key enzyme in lipolysis, was decreased in the pancreatic stroma of EL-Kras G12D /PEDF-deficient mice.…”
mentioning
confidence: 99%
“…The interactions between MMP-2 and PEDF were further demonstrated in a more recent study by [43] which identified that PEDF-deficient mice models with pancreatic tumours displayed increased levels of the proteins MMP-2 and/or MMP-9. Therefore, these findings indicate an inverse correlation between PEDF and MMP-2 during hypoxia and pancreatic cancer, which we hypothesize to occur via MT1-MMP and its activation of MMP-2, though further studies are warranted to confirm this hypothesis.…”
Section: The Regulatory Interactions Between Pedf Mt1-mmp and Mmp-2mentioning
confidence: 97%